2006
DOI: 10.1152/ajpgi.00460.2005
|View full text |Cite
|
Sign up to set email alerts
|

The transcription factor interferon regulatory factor-1 mediates liver damage during ischemia-reperfusion injury

Abstract: Hepatic ischemia occurs in the settings of trauma, transplantation, and elective liver resections. The initiating events that account for local organ damage are only partially understood. Interferon (IFN) regulatory factor-1 (IRF-1) is a transcription factor that regulates the expression of a number of genes involved in both innate and acquired immunity; however, its function in liver injury is unknown. Therefore, the purpose of this study was to investigate the role of IRF-1 in hepatic ischemia-reperfusion (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
64
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 69 publications
(73 citation statements)
references
References 43 publications
9
64
0
Order By: Relevance
“…IRF-1 has been shown to be expressed in cultures of primary hepatocytes in response to inflammatory cytokine IFN-a/b, IFN-g, TNF-a, and IL-1b (25). Recent work in our laboratory suggested that IRF-1 contributes to liver damage induced by warm hepatic I/R injury (26,27). Furthermore, we have also shown that IRF-1 plays a critical role in liver transplant preservation injury (27,28).…”
supporting
confidence: 57%
See 2 more Smart Citations
“…IRF-1 has been shown to be expressed in cultures of primary hepatocytes in response to inflammatory cytokine IFN-a/b, IFN-g, TNF-a, and IL-1b (25). Recent work in our laboratory suggested that IRF-1 contributes to liver damage induced by warm hepatic I/R injury (26,27). Furthermore, we have also shown that IRF-1 plays a critical role in liver transplant preservation injury (27,28).…”
supporting
confidence: 57%
“…Recent evidence also suggests an important role of NKT cells in initiating injury following hepatic warm I/R, as well as limiting liver graft survival following transplantation (12,13,15,41). We have previously shown that IRF-1 expression is upregulated in the liver following both warm and cold I/R injury, and increased IRF-1 expression contributes to the hepatic damage whereas the IRF-1 knockout mice were protected from the injury (26,27). Importantly, it was the specific presence of IRF-1 in the donor liver graft, but not the recipient host, that accounted for the liver damage (27,28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Several reports have investigated the roles of IRF1 and IRF3 in liver IRI. 7,8 However, to the best of our knowledge, there are no data supporting the involvement of IRF5 during liver IRI. Therefore, this study was carried out to investigate the role of the TLR4/IRF5 signaling pathway in the hepatic IRI model, by evaluating mRNA expression levels of TLR4/IRF5 axis and its downstream genes, including tumor necrosis factor alpha (TNF-α), interleukin 6 (IL-6), and interleukin 1β (IL-1β).…”
Section: Introductionmentioning
confidence: 94%
“…5 This cytokine is expressed at high levels in vascular lesions and regulates functions and properties of all of the cell types in vascular wall 6,7 by activating signal transducer and activator of transcription-1 (STAT1) and IFN regulatory factor-1 (IRF-1), the major transcriptional activator mediating IFN-␥ signal. 5 IFN-␥ is a known regulator of intercellular adhesion molecule (ICAM)-1 8,9 and plateletderived growth factor (PDGF) ␤-receptor (PDGFR-␤), 4,10 molecules that mediate SMC proliferation. However, IFN-␥ also has anti-inflammatory actions, such as interleukin-8 induction, in a range of cell types 7 and antiproliferative action in cultured SMCs.…”
mentioning
confidence: 99%